Penerapan Asas Kebebasan Berkontrak Dalam Perjanjian Jual Beli Dikaitkan Dengan Batalnya Suatu Perjanjian Disebabkan Oleh Wanprestasi - Tri Mulyani (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2016)
The aim of this research is to answer the legal issues regarding the implementation of freedom of contract principles in purchase agreement associated with cancellation of agreement which caused by breach of contract. Research specifications are normative legal research using secondary data. The type of data is qualitative data obtained from primary legal materials, secondary legal materials, and tertiary legal materials. Stages of research through library research which aims to study, examine, and trace secondary data. Data collection techniques are literature studies that are collecting and analyzing secondary data recognizing the object of research. Data obtained, grouped and arranged systematically and for further data are analyzed, in qualitative analysis.The research results showed that (1) Associated with the fundamental freedom of contract, the prohibition to override Article 1266 and Article 1267 Civil Code, a breach of fundamental contractual freedom itself. Moreover, the Law Covenant set forth in Civil Code profess open system which means that the other conditions hold, as long as no breach of the principle of propriety, custom or law (Article 1339 Civil Code); and (2) The reason a lot of the particular actors to override Civil Code Article 1266 and 1267 in a deal for his business needs often as interpretations that embrace open systems Testament Law. Clauses in it only as a complement. So, the parties may establish other conditions, provided that no violation of the principles of propriety, custom or law (Article 1339 Civil Code).